The Effect of E-Portfolio in Project-Based Learning toward Learner Autonomy and Writing Competency - Devi Ariningsih, Ni Ketut; Artini, Luh Putu; Marsakawati, Ni Putu Era (Journal of Education Reseach and Evaluation, 2021)
The National Education objectives can be achieved through learning process and a valid assessment process. Assessment has a strong involvement in the learning process. The purpose of this study is to investigate the effect of e-portfolio in project-based learning toward learner autonomy and writing competency experienced by X MIPA students of SMA Negeri 7 Denpasar. The research design was post-test only control group design. The research instruments used were questionnaire and writing test. Questionnaire was used to test learner autonomy, while writing test was used to test studentsâ€™ writing competency. Data were analyzed by employing One-way Anova and Manova. The results of this study showed that there is a significant effect of E-portfolio in Project-Based Learning toward learner autonomy and writing competency of X MIPA students of SMA Negeri 7 Denpasar. The mean score of students who were taught by using e-portfolio in project-based learning strategy is higher than the mean score who were taught by using conventional strategy. E-portfolio in Project-Based Learning also revealed potentially promotes studentsâ€™ creativity, problem solving skills, and communication through technology skills.Â